Pemanfaatan Teknologi Artificial Intelligence (AI) DeepSeek dan Connected Papers bagi mahasiswa dalam menyelesaikan Tugas Akhir - Husein, Hartina; Usmany, Paul; Putuhena, Hempry (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The development of Artificial Intelligence (AI) has entered all levels of society. The academic world is greatly affected by this development. This activity aims to provide an understanding of AI tools, namely DeepSeek and Connected Papers for students to be able to complete their final assignments. With a good understanding of these two tools, students can complete their final assignments effectively. This activity was carried out boldly using zoom and was invited by 25-30 participants. Participants in this activity are students who are completing their final assignments. This activity consists of three stages, namely evaluation before training, delivery of materials, and evaluation after training. The evaluation results showed an increase in understanding and how DeepSeek and Connect Papers work for students who had never heard of these two tools. This activity is expected to be carried out periodically and use different tools so that it becomes an alternative way for students to work in compiling final assignments effectively